2018
DOI: 10.1007/s12010-018-2713-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypericum japonicum: a Double-Headed Sword to Combat Vector Control and Cancer

Abstract: Mosquito control with naturally derived herbal insecticides has gained much momentum, with the increased insecticide resistance of vectors and the multiple infectious diseases spread by them. Yet, recent studies also suggest that mosquitoes could probably transmit some cancerous cells or cancer-causing viruses from one individual to another between their blood meals. The current research thus focused on the screening and characterization of novel plants with both mosquitocidal and anticancerous properties. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…These results were also confirmed by a third study [56]. The data suggested that H. japonicum plant extracts at very small levels were strong cytotoxic factors.…”
Section: Figure 2 Activity Of Hyperforin (Hf)supporting
confidence: 64%
See 1 more Smart Citation
“…These results were also confirmed by a third study [56]. The data suggested that H. japonicum plant extracts at very small levels were strong cytotoxic factors.…”
Section: Figure 2 Activity Of Hyperforin (Hf)supporting
confidence: 64%
“…The dosage necessary to destroy 50% of the DLA cells for hexane extracts and petroleum ether were 38.57 and 38.89 ppm, respectively. The smallest LD50 was displayed by methanolic extract with a concentration of 60.20 ppm [56].…”
Section: Figure 2 Activity Of Hyperforin (Hf)mentioning
confidence: 95%
“…The methanolic extract proved the most active, its purified fraction displaying LC 50 0.95 μg/mL. The major constituents of this active fraction were isopropyl palmitate ( 19 ), 2,4-Di- tert -butylphenol ( 20 ) and hydrocinnamic acid ( 21 ) [ 97 ]. Similarly active, the Nerine sarniensis (L.) Herb.…”
Section: Organic/aqueous Extractsmentioning
confidence: 99%
“…64.58 µg/mL), ethyl acetate (LC50 72.77 µg/mL), chloroform (LC50 88.20 µg/mL) and benzene (LC50 97.03 µg/mL)[103]. Extracts of three other species obtained from the same plant part with different organic solvents were also evaluated.The methanolic extracts were the most active: Acalypha alnifolia Klein ex Willd.…”
mentioning
confidence: 99%
“…27 Hence, currently, the scientific community has drawn attention from natural products since the plants have been a prominent source of traditional medication with the tiniest toxicity to domestic animals and mankind. 21,22 An inevitable effect of phytochemical exposure to mosquito larvae is cellular and metabolic damage. The introduction of phytochemicals from plant extract or natural insecticides may augment Reactive Oxygen Species (ROS).…”
Section: Introductionmentioning
confidence: 99%